A Probability Model of PV for the Middle-term to Long-term Power System Analysis and Its Application. (December 2016) - Lv, Yaotang; Guan, Lin; Tang, Zongshun; Zhao, Qi
Abstract: This paper proposes a probability model for the Photovoltaic (PV) power output which is adaptive for the middle-term to long-term power system analysis. In the first step, a discrete random time series model for the mean value of hourly solar irradiance is presented according to meteorology models. Then a Beta distribution model works to describe the stochastic vibration of the hourly solar irradiance around its mean value. The proposed model can describe the long term behavior of PV generator and has the advantages of less parameters and lower requirements on PV history data. It can also effectively reflect the correlation among PV generators and loads related to locations and life styles. An example of PV location and capacity selection on a distribution feeder is presented to illustrate the application and the feasibility of the model. The proposed model is applicable in power system planning, reliability analysis and many other power system long-term analyses with PV sources.